Fatty liver and mortality: a cohort population study in South Italy. Issue 6 (20th June 2019) - Caruso, Maria Gabriella; Veronese, Nicola; Notarnicola, Maria; Cisternino, Anna Maria; Reddavide, Rosa; Inguaggiato, Rosa; Guerra, Vito; Donghia, Rossella; Logroscino, Antonio; Rotolo, Ornella; Chiloiro, Marisa; Leandro, Gioacchino; et al.
Abstract : Objective: Alcoholic fatty liver (AFLD) and non-alcoholic fatty liver (NAFLD) are two common conditions. However, if they can increase the risk of death is poorly explored. We therefore aimed to investigate the potential association between the presence and severity of liver steatosis and mortality in a large sample of older people. Design: Prospective. Setting: Community. Participants: Women and men randomly sampled from the electoral rolls of the population of Castellana Grotte, a town in Southern Italy (Apulia region) between 2005 and 2006. Among 1942 initially contacted, 1708 (=87.9%) participated to the baseline survey (Multicentrica Colelitiasi III (MICOL III)). This specific study included 1445 older participants (mean age=65.2 years, females=44.2%). Exposure: NAFLD or AFLD. Primary and secondary outcomes: Mortality (all-cause and specific-cause). Results: After a median of 12 years, 312 participants (=21.6%) died. After adjusting for nine potential confounders, the presence of steatosis was not associated with any increased risk of death in both NAFLD and AFLD. The severity of liver steatosis was not associated with any increased risk of mortality in NAFLD, while in AFLD, the presence of moderate steatosis significantly increased the risk of overall (HR=2.16; 95% CI 1.19 to 3.91) and cancer-specific (HR=3.54; 95% CI 1.16 to 10.87) death. Conclusions: Liver steatosis is not associated with any increased risk of death in NAFLD, while moderate steatosis could be a risk factor for mortality (particularly due to cancer) in people affected by AFLD.